SNAr Reaction/Claisen Rearrangement Approach to 2,4-Diisoprenylxanthones: Total Synthesis of Garcinone A - Mochizuki, Miho; Fujimoto, Yuuki; Yanai, Hikaru; Matsumoto, Takashi (Synlett, 2020)
A total synthesis of garcinone A, a natural xanthone possessing a 2,4-diisoprenylated structure, was accomplished by utilizing a readily available 1,3-difluoroxanthone derivative as the key intermediate through the installation of two isoprenyl side chains by an SNAr reaction with the alkoxide of 1,1-dimethylallyl alcohol followed by a Claisen rearrangement. The strategy also permitted the selective installation of mutually different allylic moieties at the C2 and C4 positions.
Keywords: natural product synthesis; xanthones; isoprenylation; SNAr reaction; Claisen rearrangement; garcinone A